A catalog of the types of Geotrupidae, Glaresidae, Hybosoridae, Lucanidae and Trogidae (Insecta: Coleoptera: Scarabaeoidea) deposited in the Museo Argentino de Ciencias Naturales, Buenos Aires - Bachmann, A.O. (2010)
A catalog of the types, all current categories, of Geotrupidae, Glaresidae, Hybosoridae, Lucanidae and Trogidae, housed in this Museum, is given; it comprises the types of 40 names; 39 (98%) of them are here represented by name-bearing types («primary types»).